The politics of numbers: explaining recent challenges at the Australian Bureau of Statistics. Issue 1 (2nd January 2019) - Howard, Cosmo
ABSTRACT: The Australian Bureau of Statistics (ABS) has experienced several significant challenges in recent years, including a declining operating budget, criticisms of its technical capability and concerns about political interference. In-depth interviews were conducted with senior ABS and Treasury Department officials to obtain their perspectives on the causes of the agency's difficulties. Interview data were interpreted using frameworks from the political science literature on delegation, including the principal-agent paradigm, models of bureaucratic strategy and the public service bargains approach. The study finds that the principal-agent perspective does not help to explain the ABS's difficulties, but that problems of administrative strategy and tacit bargains between the government and the ABS have contributed significantly to the agency's challenges. The findings provide insights into the politics of official statistics, and shed light on the evolving role and status of expertise in Australian politics and government.